Keragaman Gen Myxovirus (Mx) pada Ayam Kampung Terseleksi Polymorphisms of Myxovirus Gene in Selected Kampung Chicken - Permatasari, P.; Sumantri, C.; Darwati, S.; Ulupi, N. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
The Mx gene is wellknown as marker genetic for chicken resistance of virus infection. The aim of this study was to analyze the mx gene polymorphisms in selected kampung chicken. A total of 25 heads of kampung chicken, which had been selected for ND virus resistant, were identified by PCR-RFLP method.The Mx gene used Hpy8I restriction enzyme where digested at GTN|NAC nucleotides. There were two  alleles, A and G with three genotypes AA, AG dan GG. The result showed that 69.2% of kampung chicken were resistant toward the virus infection. This population was in Hardy-Weinberg equilibrium (x2< x20.05).Keywords: polymorphisms, Mx gene, selected kampung chicken